Sacro e profano: rituali trasgressivi in Camere separate di Pier Vittorio Tondelli - Janusz, Joanna (Romanica Silesiana)
In the last book by Pier Vittorio Tondelli, Camere separate, the ritual motif appears in its two essential aspects: sacrum — as a relation between the main protagonist and the religious‑mystic sphere; and profanum as a relation between the main protagonist and society. Both traditional aspects of ritual are negated and distorted. The first, the religious‑mystic sphere, is negated by the protagonist himself. He rejects Catholic dogmatics and rituals because he finds no place for them alongside his homosexuality. This rejection prompts him to work out his own individual religiousness in which contact with God does not require any rituals. In terms of the social aspect, the protagonist is excluded from the society in which he lives. Social norms preclude him from participating in rituals such as marriage or mourning for the dead. This negative confrontation with ritual and social custom allows the protagonist to develop a new, more mature self‑awareness which allow him to accept the imminence of suffering and death. Key words: Tondelli, ritual, transgression, initiation, mourning